PENILAIAN KINERJA DEPARTEMEN PRODUKSI DALAM MENERAPKAN REVERSE LOGISTICS DENGAN PENDEKATAN ANALYTICAL HIERARCHY PROCESS DAN DATA ENVELOPMENT ANALYSIS (Studi Kasus Di Pt Sinar Sosro Kantor Pabrik Mojokerto) - Riska Septifani; Usman Effendi; Ika Atsari Dewi (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2012)
Reverse logistics is process of controlling the flow of raw materials, finished products and related information of the consumption activities to capture the value of product returns. PT Sinar Sosro Mojokerto Factory Office applies reverse logistics by producing tea-based beverages in returnable glass bottling (RGB). The research objectives was to determine the weight of each variable to assess performance of the Production Department in implementing reverse logistics with Analytical Hierarchy Process (AHP), to assess performance or efficiency of production processes for each product types with Data Envelopment Analysis (DEA) and made projections for the improvement of inefficiency production by using the input-oriented CCR projection. The method used was incorporation of AHP and DEA in production of six types of RGB products (Teh Botol Sosro, Joy Tea, Tebs, S-tee, Fruit Tea Apple and Fruit Tea Black Currant) for 20 months (January 2010-August 2011). Variables for assessment are input and output variable. The results showed weight of both, input and output variables were 0.5. Input variables subcriterias from the biggest until smallest weight namely inhibition of production, paid hour nonstandart bottles, broken bottles, fully nonstandart bottles and losses with successive weights of 0,185, 0,160, 0,055, 0,050, 0,030 dan 0,020. Output variable subcriterias from the biggest until smallest weight namely production,  mechanical efficiency, line utility, line efficiency and volume with successive weights of 0,265, 0,085, 0,070, 0,060, dan 0,020. The performance assessment showed, 18 production processes were inefficient. Inefficient production process could be improved with input-oriented CCR projection, by optimizing the value of the input and output variable subcriterias.Keywords: Performance Assessment, Reverse Logistics, AHP, DEA